2008
DOI: 10.1161/circulationaha.108.792903
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Kidney Disease and Blood Pressure on the Development of Cardiovascular Disease

Abstract: Background-Kidney disease is associated with an increased risk of cardiovascular disease (CVD); however, there have been few well-designed prospective studies of this issue in Asian populations. Recent epidemiological studies have suggested that a lower blood pressure level may be associated with an increased risk of CVD in individuals with kidney dysfunction. Methods and Results-Using data from 10 community-based cohort studies in Japan, we conducted follow-up on a total of 30 657 individuals 40 to 89 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(50 citation statements)
references
References 28 publications
3
46
0
1
Order By: Relevance
“…Reports from Japan showed that 7-19% of adults have chronic kidney disease. [9][10][11]18,20 In addition, among Japanese patients with chronic heart failure or sleep-related breathing disorder, the prevalence of chronic kidney disease was reported to be 26.7 or 30.5%, respectively. 12,13 In this study, the prevalence of chronic kidney disease in all patients visiting our hospital (n¼6562), in patients with CAD (n¼797) or in patients with acute coronary syndrome (n¼291) was 19.9, 29.5 and 31.6%, respectively.…”
Section: Prevalence Of Chronic Kidney Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Reports from Japan showed that 7-19% of adults have chronic kidney disease. [9][10][11]18,20 In addition, among Japanese patients with chronic heart failure or sleep-related breathing disorder, the prevalence of chronic kidney disease was reported to be 26.7 or 30.5%, respectively. 12,13 In this study, the prevalence of chronic kidney disease in all patients visiting our hospital (n¼6562), in patients with CAD (n¼797) or in patients with acute coronary syndrome (n¼291) was 19.9, 29.5 and 31.6%, respectively.…”
Section: Prevalence Of Chronic Kidney Diseasementioning
confidence: 99%
“…7,8 In real medical practice, physicians should always consider renal dysfunction in patients with preexisting or suspected CAD as a significant predictor. Although the prevalence of an estimated glomerular filtration rate (eGFR) in the general Japanese population, [9][10][11] patients with heart failure 12 or patients with sleep-related breathing disorder 13 has been reported earlier, the prevalence of chronic kidney disease and long-term prognosis in Japanese patients with CAD based on the eGFR value are less well identified.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 An estimated 13% of the Japanese adult population has CKD. 5,6 Several Japanese studies have indicated that the hazard ratio of the onset of myocardial infarction (MI) is 2.5-fold higher among Japanese men with CKD and without previous cardiovascular diseases (CVD) than in those without CKD 7,8 and in a Japanese population with eGFR \50 mL/minute/1.73 m 2 . 8 Although coronary angiography (CAG) has been the gold standard for detecting coronary artery disease (CAD), contrast media-induced nephropathy or cholesterol microembolization is serious adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…In the Japan Arteriosclerosis Longitudinal Study 28) , Ninomiya et al calculated the risk of myocardial infarction, stroke, combined CVD, and all-cause mortality associated with reduced GFR in 30657 Japanese individuals 40 to 89 years of age without preexisting CVD or kidney failure. The age-and sex-adjusted hazards ratios for myocardial infarction, stroke, combined CVD, and all-cause death in subjects with GFR <60 mL/min/1.73 m 2 as compared with those with GFR ≥ 90 mL/min/1.73 m 2 were 3.35 (1.94-5.79), 2.06 (1.51-2.81), 2.26 (1.71-2.99), and 1.70 (1.44-2.00), respectively.…”
Section: Epidemiology Of Ckd and Cvd In Western Countriesmentioning
confidence: 99%